Therapeutic effects of curcumin and piperine combination in critically ill patients with sepsis: a randomized double-blind controlled trial - Babak Alikiaii; Narges Khatib; Mohaddeseh Badpeyma; Esmat Hasanzadeh; Saeed Abbasi; Sepide Amini; Zahra Kiani; Shirin Hassanizadeh; Zahra Iraj; Amirhossein Sahebkar; Anju Majeed; Mohammad Bagherniya (Trials)
Abstract Background Sepsis, an organ dysfunction caused by deregulated host response to infection, is a major health problem worldwide. Sepsis is associated with high rates of mortality, especially in critically ill patients. Curcumin may improve sepsis through its anti-inflammatory and antioxidant effects. This study aimed to investigate the effects of curcumin-piperine administration in critically ill septic patients. Method This double-blind randomized controlled trial (RCT) conducted on 66 patients with sepsis hospitalized in the intensive care unit (ICU). Patients were randomized to either the intervention group receiving two tablets of curcumin-piperine (each containing 500 mg curcuminoids and 5 mg piperine) (n = 33), or the placebo group receiving two matched tablets of placebo (n = 33) daily for 7 consecutive days along with enteral feeding. Clinical, laboratory, and biochemical indices were evaluated before and after the intervention. Statistical analyses were performed based on an intention-to-treat method. Result Mortality was observed in 10 patients in the curcumin-piperine group, and 12 patients in the control group. Curcumin-piperine significantly reduced bilirubin-total (P = 0.02), bilirubin-direct (P = 0.02), pH (P < 0.001), C-reactive protein (P = 0.04), erythrocyte sedimentation rate (P < 0.001), and platelet count (P = 0.01) compared with the placebo. A significantly lower reduction was found in red blood cell (P = 0.003), hemoglobin (P = 0.001), and hematocrit (P = 0.002) levels in the intervention vs. placebo group. In addition, mean corpuscular hemoglobin (P < 0.001) and mean corpuscular hemoglobin concentration (P = 0.001) were significantly higher in the intervention vs. placebo group. Conclusion Curcumin–piperine supplementation over a short period had beneficial effects on some inflammatory and laboratory indices in critically ill patients with sepsis. Trial registration IRCT20150613022681N4; available on: https://en.irct.ir/trial/52661 . Registration date: 2021-01-02, 1399/10/13.